Wearable Sensor-Based Detection of Influenza in Presymptomatic and Asymptomatic Individuals. (27th June 2022) - Temple, Dorota S; Hegarty-Craver, Meghan; Furberg, Robert D; Preble, Edward A; Bergstrom, Emma; Gardener, Zoe; Dayananda, Pete; Taylor, Lydia; Lemm, Nana-Marie; Papargyris, Loukas; McClain, Micah T; Nicholson, Bradly P; et al.
Abstract: Background: The COVID-19 pandemic highlighted the need for early detection of viral infections in symptomatic and asymptomatic individuals to allow for timely clinical management and public health interventions. Methods: Twenty healthy adults were challenged with an influenza A (H3N2) virus and prospectively monitored from 7 days before through 10 days after inoculation, using wearable electrocardiogram and physical activity sensors. This framework allowed for responses to be accurately referenced to the infection event. For each participant, we trained a semisupervised multivariable anomaly detection model on data acquired before inoculation and used it to classify the postinoculation dataset. Results: Inoculation with this challenge virus was well-tolerated with an infection rate of 85%. With the model classification threshold set so that no alarms were recorded in the 170 healthy days recorded, the algorithm correctly identified 16 of 17 (94%) positive presymptomatic and asymptomatic individuals, on average 58 hours postinoculation and 23 hours before the symptom onset. Conclusions: The data processing and modeling methodology show promise for the early detection of respiratory illness. The detection algorithm is compatible with data collected from smartwatches using optical techniques but needs to be validated in large heterogeneous cohorts in normal living conditions. Clinical Trials Registration . NCT04204493. Abstract : In this human-challenge study, participants were monitored using wearable electrocardiogram sensors integrated with accelerometers. A semisupervised machine learning algorithm detected the infection in both symptomatic and asymptomatic individuals, on average 23 hours before the onset of symptoms.